Metabolic Parameters of Post-COVID Patients in a Tertiary Care Hospital in Bangladesh (Journal of Medicine, 2025)
Background: COVID-19 has led to lasting health impacts, including post-COVID syndrome, persistent symptoms beyond three months. SARS-CoV-2 affects various metabolic pathways, contributing to chronic sequelae.This study examines metabolic parameters among post-COVID patients in Bangladesh, focusing on clinical and laboratory findings. Methods: A cross-sectional study of 236 patients with post-COVID-19 syndrome was conducted at the Respiratory Medicine Department of Bangladesh Medical University, from August 2021 to July 2022. Clinical symptoms and physical measurements (height, weight, BMI) were recorded. Parameters assessed included WBC count, platelet count, serum ferritin, blood glucose, HbA1c, serum creatinine, serum electrolytes, and fasting serum lipid profile. Data were analyzed using SPSS 26 version, with t-tests, Chi-square, and Fisher’s exact tests. Results: The study revealed significant alterations in metabolic parameters post-COVID. Mean WBC count was 9,000 cells/mm (SD=2,500), while mean platelet count was 200,000 (SD=30,000). Mean serum ferritin levels were elevated to 550 ng/mL (SD=200). A significant increase in blood glucose was noted, with a mean of 140 mg/dL (p